Prototyping Intelligent IoT Smart Hubs on Repurposed TV Boxes: A Low-Cost Approach to Practical Engineering Education - Silva, Cláudio R. M.; Santos, João Paulo N. dos; Silva, Felipe Augusto C. M. (Anais do Workshop on Sustainable Computing and Technology Reuse (SCoRe); 2025: Anais do I Workshop on Sustainable Computing and Technology ReuseDO - 10.5753/score.2025.16970, 2025)
Digital Transformation and the Internet of Things (IoT) are interrelated concepts. These initiatives have substantially expanded the capabilities of IoT, rendering such systems more intelligent and autonomous across diverse automation domains. Although these advances have had considerable impact across industrial, residential and commercial domains, they also have presented interesting opportunities and challenges within educational environments. The reason for this is a growing demand for curricula that foster practical competencies, enabling students to design, implement and interact with intelligent, networked systems. This work presents the design and implementation of a low-cost IoT smart hub based on modified TV boxes, featuring natural language support through integration with NLP tools. The methodology consists of a prototyping approach that involves a set of validation tests on a control plant defined in an educational environment. The results have shown that the implementation is technically viable and pedagogically effective for hands-on engineering education.